Multiplex Real-Time PCR Assay for Detection of Influenza and Human Respiratory Syncytial Viruses - Boivin, Guy (J Clin Microbiol, 2004)
A multiplex real-time PCR assay was developed with a LightCycler instrument for detection of influenza viruses A and B and the human respiratory syncytial virus (HRSV). Detection of each viral product and of an internal control was based on determination of specific melting temperatures by the LightCycler software. The lower limit of detection in the multiplex PCR assay was found to be 50 copies for each viral target. In an evaluation of nasopharyngeal samples collected from hospitalized children (ages, 0 to 3 years) with acute respiratory tract infections during the winter of 2001 to 2002, a viral pathogen was detected by the multiplex PCR test in 139 (66.8%) of 208 cases, including 45 (21.6%) influenza A virus infections, no (0%) influenza B virus infections, 106 (51%) HRSV infections, and 12 (5.8%) coinfections. The multiplex PCR test was compared to rapid antigen detection assays for influenza viruses A and B (Directigen; Becton Dickinson, Sparks, Md.) and HRSV (RSV TestPack; Abbott Laboratories, Abbott Park, Ill.) in 172 and 204 samples, respectively. After resolution of discrepant test results by use of additional PCR assays targeting other viral genes, the sensitivity (Se) and specificity (Sp) of the multiplex PCR assay for influenza A virus were 100 and 97.7% compared to 43.6 and 98.5% for the antigenic test. Similarly, the Se and Sp of the multiplex PCR assay for HRSV were 94.5 and 98.9% compared to 81.6 and 94.7% for the antigenic test. In conclusion, our multiplex real-time PCR assay combines both rapidity and sensitivity for detecting the most important respiratory viral pathogens in children.